2012
DOI: 10.1111/j.1740-1461.2012.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

The Secret of My Success: How Status, Eliteness, and School Performance Shape Legal Careers

Abstract: If we study the 40,000 law graduates who join the legal profession each year, how well can we predict their future careers? How much of their future is predicted by their social class? The law school they attend? Their law school grades? This article undertakes the first in‐depth examination of these questions. Drawing on several large and recently released data sets, we examine the role of class, school prestige, and law school grades on the career earnings of lawyers and the success of big firm associates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…As Henderson and Zahorsky (2012) point out, "Snobbishness and elitism are the last socially acceptable prejudices". In contradistinction, an empirical study by Sander & Yakowitz (2012) found that, generally speaking, grades were a more significant predictor of success in employment than the status of the school attended, although this appears to exclude the Ivy League law schools.…”
Section: Ranking Researchmentioning
confidence: 88%
“…As Henderson and Zahorsky (2012) point out, "Snobbishness and elitism are the last socially acceptable prejudices". In contradistinction, an empirical study by Sander & Yakowitz (2012) found that, generally speaking, grades were a more significant predictor of success in employment than the status of the school attended, although this appears to exclude the Ivy League law schools.…”
Section: Ranking Researchmentioning
confidence: 88%
“…Other scholars have highlighted the impact of law school prestige on attorneys’ career prospects (Dinovitzer, ). Kay and Hagan (:498–99) conclude that “[t]he contacts that elite law school students make through their schooling play a significant role in shaping their career path.” To account for the influence that law school experiences may play on later professional experiences and career satisfaction, we follow the approach of prior studies by including categories based on the U.S. News and World Report 's law school rankings (Dinovitzer and Garth, ; Dinovitzer, ; Sander and Bambauer, ). These are broken down into six categories, which track the law school rankings, with our excluded category being those considered “fourth tier” (ranked above 150).…”
Section: Methodsmentioning
confidence: 99%
“…Social class was revealed to be a substantial factor in law school enrollment (Stevens, ). Moreover, as discussed above, the status of law school attended affects the future careers of law graduates (Sander and Bambauer ). Yet, Sander and Bambauer () showed that grades in law school mitigate the effects of law school status and similar trends were also found in the United Kingdom (Nicholson ).…”
Section: Hierarchy and Stratification In The Legal Professionmentioning
confidence: 99%
“…Moreover, as discussed above, the status of law school attended affects the future careers of law graduates (Sander and Bambauer ). Yet, Sander and Bambauer () showed that grades in law school mitigate the effects of law school status and similar trends were also found in the United Kingdom (Nicholson ). The Canadian structure of law schools is somewhat different, barring comparison on this issue to the United States and the United Kingdom.…”
Section: Hierarchy and Stratification In The Legal Professionmentioning
confidence: 99%